Implementación de la tecnología Blockchain para la validación de autenticidad de los certificados académicos digitales / Blockchain technology implementation for the authenticity validation of digital academic certificates. - Sánchez Malla, Edgar Patricio (2022)
The objective of this Degree Project (DP) aims to implement a software module for the authenticity validation of digital academic certificates applying blockchain technology in Universidad Nacional de Loja's Events system. In which it is based on the agile blockchain DApp engineering (ABCDE) methodology throughout its different phases, allowed to complete the DP. In the first stage, the phases of the ABCDE methodology which were involved are: defining the objective; the actors involved; user history and requirements; architecture diagram and the division into two subsystems (smart contracts and applications) of software module. In the second stage, the design, codification and unit testing phases were executed for each subsystem. In the third stage the phases carried out were integration, functional and acceptance tests; jointly with the software module deployment in Ethereum Rinkeby test net. The technologies used for the development are Truffle Suite with the React box, Solidity, MetaMask, Ethereum; which were eventually implemented in the Microsoft Azure cloud computing service. Even though the latter is not contemplated within the Degree project, its culmination is left in evidence. Finally, the developed software module allows to carry out the authenticity validation of digital academic certificates efficiently and correctly. Simultaneously, it allows them not to be counterfeited, in contrast to the traditional way in which they are validated with multiple reliability and security problems of a centralized system information. Keywords: [ABCDE, blockchain, smart contracts, DApp, software development, ethereum, react, truffle].